A STRATEGY FOR THE RAPID IDENTIFICATION OF FUNGAL METABOLITES AND THE DISCOVERY OF THE ANTIVIRAL ACTIVITY OF PYRENOCINE A AND HARZIANOPYRIDONE - Ioca, Laura P.; Romminger, Stelamar; Santos, Mario F. C.; Bandeira, Karin F.; Rodrigues, Fabiana T.; Kossuga, Miriam H.; Nicacio, Karen J.; Ferreira, Everton L. F.; Morais-Urano, Raquel P.; Passos, Messias S.; Kohn, Luciana K.; Arns, Clarice W.; et al. (Soc Brasileira Quimica, 2016)
The isolation and identification of bioactive metabolites from complex extracts obtained from microbial growth media is a time consuming, costly, and labor-intensive task. A strategy to rapidly identify secondary metabolites isolated from extracts obtained from the culture media of marine-derived and endophytic fungal strains is described. Identification was achieved by HPLC-UV-MS and H-1 NMR analyses in combination with data obtained from the Dictionary of Natural Products. Among the compounds identified, (-)-naphthoquinoneimine, citreorosein, emodin, pyrenocine A and harzianopyridone displayed moderate to potent antiviral activity. (-)-Naphthoquinoneimine was isolated as the enantiomer of its previously reported dextrorotatory congener, while 6,7-dihydroxy-2,2- dimethyl-4-chromanone is herein reported for the first time as a natural product.
Keywords: fungal metabolites; rapid identification; dereplication; antiviral